N-type large single crystal diamond with S doping and B-S co-doping grown in FeNi–C system. (June 2019) - Wang, Jiankang; Li, Shangsheng; Cui, Jinlei; Feng, Lu; Yu, He; Su, Taichao; Hu, Meihua; Yu, Kunpeng; Han, Fei; Ma, Hongan; Jia, Xiaopeng
Abstract: The n-type semiconductor large single diamonds with S doping and B-S co-doping were successfully synthesized in FeNi-C system at the constant conditions about temperature 1250 °C and pressure 5.6 GPa. In this study, the effects of different additive amounts of FeS doping alone and B-FeS co-doping on the crystal shape, crystal face, color and quality of diamonds were investigated. The influence of B-FeS co-doping on the V-shaped region of diamond growth is greater than that of FeS-doping diamond. The color of FeS doping crystals change from bright yellow to bright green and then appear grayish yellow. On the contrast, the color of B-FeS co-doping diamond changes from yellowish green to grayish green and black. We found that our obtained diamond contains B/S/N elements, and S exists in C-S-O forms in diamond lattice. Besides, as the increasing amount of additive B, the content of S/N relative to C is also improved. FeS instead of S as an additive is more conducive to incorporation of S into diamond than that in previous studies. The results of Hall Effect measurement showed that diamonds with FeS single-doping and B-FeS co-doping are n-type semiconductors. B-FeS co-doping not only contributes to improvement Hall mobility and carrier density but the reduction of resistance in diamond. The previous study of the first-principles calculation for n-type B-S co-doping and S-doping diamond was verified experimentally by synthesizing FeS-doping and B-FeS co-doping large single crystal diamonds in this paper. This work helps to further understand the mechanism of the synthesis and electrical properties of B-FeS co-doping and FeS single-doping diamond. Highlights: FeS instead of S as an additive is more conducive to the incorporation of S into diamond than that in previous studies. The calculation for n-type diamonds with S-doping and B-S co-doping is verified by growing diamonds with FeS as S source. The minimum resistivity of B-FeS co-doping diamond is 9.62 × 10 4 Ω·cm, and its maximum Hall mobility is 1092.516 cm 2 /Vs.